Biocomponents from Opuntia robusta and Opuntia streptacantha fruits protect against diclofenac-induced acute liver damage in vivo and in vitro. (February 2022) - Villa-Jaimes, Gloria Stephanie; Aguilar-Mora, Fabio Alejandro; González-Ponce, Herson Antonio; Avelar-González, Francisco Javier; Martínez Saldaña, Ma. Consolación; Buist-Homan, Manon; Moshage, Han
Graphical abstract: Highlights: Diclofenac induces acute-liver damage causing oxidative stress by mitochondrial dysfunction. Opuntia extracts prophylactically protect against diclofenac-induced acute liver toxicity. The protective effect of Opuntia extracts is related to their antioxidant properties to prevent cell dysfunction and death. Antioxidant activity of Opuntia extracts is due to their biocomponents content such as betacyanins. Abstract: This study aimed to investigate whether Opuntia spp- extracts protect against diclofenac (DF)-induced hepatotoxicity. Rats were pretreated with Opuntia extracts, betanin (Bet) and N-acetylcysteine (NAC) followed by a single challenge of diclofenac. Liver tissue was collected for biochemical and histological analysis. Primary rat hepatocytes were treated with diclofenac (400 µmol/L) with and without pretreatment with Opuntia extract. Apoptosis was measured by caspase-3 activity and necrosis by Sytox green staining. RNA was isolated, and real-time qPCR was performed to assess mRNA levels of stress and apoptosis-related genes MnSOD (SOD2), GADD45B and P53. ROS production was measured using the fluorescent MitoSOX assay. Results demonstrated that Opuntia spp -extracts protect against DF-induced liver toxicity via reducing oxidative stress and the inhibition of P53.